2011
DOI: 10.3318/bioe.2011.111.08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Success of Mountain Blanket Bog Pool Restoration in Terms of Aquatic Macroinvertebrates

Abstract: Peatlands in Ireland have been subject to peat extraction and drainage for many years, with detrimental effects on the fl ora and fauna of the ecosystem. Blanket bog has been listed for protection under Annex 1 of the EU habitats directive, making the conservation of intact bogs as well as the restoration of degraded sites a priority. In order to assess how effective a restoration measure this has been it is important to look at the biodiversity within the site. This study compared the macroinvertebrate and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Almost no dragonflies are found in degraded, dry, and shaded peatlands, while they immediately colonize rewetted sites with unshaded water bodies (Elo et al ) as created by peat extraction for dam building. This confirms previous findings, that showed that bog pools can be successfully restored (Mazerolle et al ; Hannigan et al ; Brown et al ). Furthermore, our results showed that deeper pools have higher dragonfly richness, including characteristic peatland species.…”
Section: Discussionsupporting
confidence: 92%
“…Almost no dragonflies are found in degraded, dry, and shaded peatlands, while they immediately colonize rewetted sites with unshaded water bodies (Elo et al ) as created by peat extraction for dam building. This confirms previous findings, that showed that bog pools can be successfully restored (Mazerolle et al ; Hannigan et al ; Brown et al ). Furthermore, our results showed that deeper pools have higher dragonfly richness, including characteristic peatland species.…”
Section: Discussionsupporting
confidence: 92%
“…It presents baseline macroinvertebrate community data on the reference condition for a range of peatland types. This will be useful for future work to select indicator species of state and impact, in terms of habitat integrity, biodiversity and success of rehabilitation efforts (Hannigan et al, 2011). To achieve this, further sampling is required along a gradient of degradation, in combination with more intensive temporal sampling.…”
Section: Discussionmentioning
confidence: 98%
“…Ditch blocking is thus unlikely to lead to either positive or negative changes in the treatability of potable water at our site. Although the lack of improved treatability may prove disappointing to water utilities, the null result can also be perceived as a "no regrets" outcome if other benefits can be obtained from ditch-blocking, for example, reducing peak flows (Ballard, McIintyre, & Wheater, 2012), reducing sediment loss (Holden, Gascoign, & Bosanko, 2007), improving biodiversity (Carroll et al, 2011;Hannigan, Mangan, & Kelly-Quinn, 2011), restoring bog vegetation (Bellamy, Stephen, Maclean, & Grant, 2012), and improving landscape aesthetics (Bonn et al, 2014), without concern that these aims will interfere with potable water supplies.…”
Section: Discussionmentioning
confidence: 99%